Human Capital Valuation in the Knowledge Economy of Kazakhstan - Janshanlo, Ramzan E.; Kogut, Oksana Yu.; Sultanova, Bakyt B.; Jakisheva, Urazgul K.; Arystambaeva, Almira Z. (The journal of contemporary issues in business and government, 2020)
The aim of this work is to provide a variety of approaches and methods for assessing the value of human capital at the macro and micro levels, which are used in the economic literature. Human capital is a resource and mechanism of the organization's innovative activity; the effectiveness of its use affects the development of the economy as a whole. The authors critically and comprehensively review the various existing methods for assessing human capital and systematize them. The study considered an example of the analysis of the human development index (HDI) in Kazakhstan. Trends in HDI formation and use have been identified, and a multifactorial regression model of HDI has been developed. The authors propose to calculate the assessment of the value of the human capital of an organization using the example of the author personally. To assess the value of human capital, it is necessary to use a cost-based methodology. The proposed method considers the initial cost of human capital of a particular employee and the cost of knowledge, acquired by him as a result of advanced training. A multifactorial correlation-regression model of the HDI has been developed.